Factors Shaping the Evolution of the Islamic Cultural History (SKI) Curriculum in Madrasahs (1973-2013) - Rofik, Rofik; Hasan, Noorhaidi; Hak, Nurul (Jurnal Pendidikan Islam, 2023)
Purpose – This research undertakes an exploration of the factors shaping the evolution and continuity of the Islamic Cultural History (SKI) curriculum in madrasahs between 1973 and 2013. It zeroes in on five predominant influences: political, economic, social, cultural, and ideological. Design/methods/approach – A historical research method was the primary tool, with data from various written records—comprising legal documents, regulations, and textbooks. A chronological lens was employed for analysis, with categorizations influenced by pertinent regulations and the prevailing zeitgeist. Findings – Of the factors, political dimensions, especially government stances and policies, took precedence in curriculum development. Furthermore, aspects like economic strides, prevailing social conditions, and national ideologies such as Pancasila (Indonesian state philosophy) bore significance in shaping the curriculum. The insights gathered suggest a pivotal role of socio-political dynamics and scientific progress in dictating madrasah curriculum changes. Research implications/limitations – While this investigation furnishes deep insights into a specific period, its temporal scope poses limitations, suggesting a potential exploration post-2013 and scrutiny of other influencing variables.